2006
DOI: 10.4067/s0717-66432006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Valor sistemático de la epidermis abaxial de la lámina foliar en especies americanas del género Trisetum Pers. (Poaceae: Pooideae: Aveninae)

Abstract: Se estudió la epidermis abaxial de la lámina foliar en 29 especies y 3 variedades del género Trisetum s.s. Adicionalmente, se incluyó a Deschampsia brasiliensis (Louis-Marie) Valencia (= Trisetum brasiliense Louis-Marie), Helictotrichon bulbosum (Hitchc.) Parodi (= T. bulbosum Hitchc.) y Peyritschia deyeuxioides (Kunth) Finot (= T. deyeuxioides Kunth). Además, se realizaron observaciones de la epidermis adaxial en algunas especies sudamericanas, utilizando microscopio electrónico de barrido (MEB). Se confeccio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…The generic placements of these two species have varied over time. Hitchcock (1927) described T. bulbosum , recorded from southern Argentina and southern Chile (Finot et al, 2006), and Parodi (1949) later transferred it to Helictotrichon Besser, as H. bulbosum (Hitchc.) Parodi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generic placements of these two species have varied over time. Hitchcock (1927) described T. bulbosum , recorded from southern Argentina and southern Chile (Finot et al, 2006), and Parodi (1949) later transferred it to Helictotrichon Besser, as H. bulbosum (Hitchc.) Parodi.…”
Section: Discussionmentioning
confidence: 99%
“…Finot et al (2005) recognized T. brasiliense as Deschampsia brasiliensis and maintained T. juergensii in Trisetum (with hesitation), and they indicated that neither of the species fits well in Trisetum . On the basis of micromorphological analysis of lemma epidermal characters, Finot et al (2006) demonstrated that neither T. brasiliense nor T. juergensii fit the generic circumscriptions of Helictotrichon, Deschampsia , and Trisetum , but they did not suggest a revised classification for these taxa. Chiapella & Zuloaga (2010) excluded Deschampsia brasiliensis from their taxonomic treatment of Deschampsia for South America and mentioned that its generic placement is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…En Trisetum las panículas son espiciformes, mientras que en D. danthonioides las panículas son laxas. Además en Deschampsia la arista dorsal está insertada en la base de la lema, por el contrario las especies de Trisetum tienen la arista dorsal insertada en la parte media de la lema (Finot et al 2005). tienen ligeras diferencias con la descripción proporcionada en la revisión del género Deschampsia (Chiapella & Zuloaga 2010).…”
Section: Figuraunclassified
“…Finot & P. M. Peterson es endémica de Ecuador, P. conferta (Pilg.) Finot se distribuye en Ecuador, Venezuela y Bolivia, y las restantes, de amplia distribución: P. deyeuxioides y P. pringlei, alcanzan su límite más austral en Ecuador (Fournier, 1886;Hitchcock, 1927;Koch, 1979;Finot, 2003;Finot et al, 2004Finot et al, , 2006.…”
Section: Introductionunclassified